IMPROVEMENT OF FINANCING OF JOINT-STOCK COMPANIES THROUGH THE STOCK MARKET (European Journal of Economics, Finance and Business Development, 2025)
This article investigates the improvement of financing mechanisms for joint-stock companies through the stock market, emphasizing the role of market-based capital in ensuring corporate sustainability and growth. As financial globalization deepens and the demand for non-debt capital rises, the stock market has become a strategic platform for joint-stock companies to attract long-term investment, reduce financial dependence on bank loans, and enhance capital efficiency. The study analyzes key factors such as expanding access to public offerings, optimizing dividend and share issuance policies, increasing transparency in corporate reporting, and building investor trust through effective governance. Attention is also given to the adoption of modern financial technologies and regulatory reforms that facilitate smoother entry and operation in stock exchanges.